First-Year Life Science Students' Understanding of the Role of Plants in the Ecosystem-A Concept Network Analysis - Ilona Södervik; Maija Nousiainen; Ismo. T. Koponen (MDPI AG, 2021)
The purpose of this study is to increase the understanding about undergraduate life science students' conceptions concerning the role of photosynthesizing plants in the ecosystem, utilizing a network analysis method. Science learning requires the integration and linking of abstract and often counterintuitive concepts successfully into multifaceted networks. The quality of these networks, together with their abilities to communicate via the language of science, influences students' success in academic, verbal problem-solving tasks. This study contributes to investigating students' understanding, utilizing a modern network analysis method in exploring first-year university life science students' written answers. In this study, a total of 150 first-year life science students answered two open-ended tasks related to the role of photosynthesizing plants in the ecosystem. A network analysis tool was used in exploring the occurrence of different-level science concepts and the interrelatedness between these concepts in students' verbal outputs. The results showed that the richness of concept networks and students' use of macro-concepts were remarkably varied between the tasks. Higher communicability measures were connected to the more abundant existence of macro-concepts in the task concerning the role of plants from the food-chain perspective. In the answers for the task concerning the role of plants regarding the atmosphere, the students operated mainly with single facts, and there were only minor interconnections made between the central concepts. On the basis of these results, the need for more all-encompassing biology teaching concerning complex environmental and socio-economic problems became evident. Thus, methodological and pedagogical contributions are discussed.